Medical tourism and modelling: a bibliometric analysis based on a Scopus database - Fernandes, Paula O. (2023)
The main goal of this paper is to systematically evaluate the bibliographic production on modelling, with an emphasis on medical and wellness tourism, to identify possible convergence of interests among health and tourism fields, from 2012 to 2021. This paper was based on a bibliometric analysis to find a relationship between medical and wellness tourism with data modelling based on a network citation analysis. The main findings showed: (i) a growing evolution of scientific production in recent years that address the medical tourism topic; (ii) a combination of important features of management of health services related to medical tourism, supported by forecasting data models may be a trend of future topics to be researched and developed as decision-making support.